2022
DOI: 10.1007/s10690-022-09386-4
|View full text |Cite
|
Sign up to set email alerts
|

The Stock Performance of Green Bond Issuers During COVID-19 Pandemic: The Case of China

Abstract: The green bond (GB) is a new financial product in the green finance field that has recently become a corporate social responsibility (CSR) tool for organizations. Previous studies show that high-CSR firms receive more trust from shareholders during a financial crisis. This paper aims to assess the stock performance of publicly listed Chinese companies that issued GBs during the COVID-19 pandemic. The bond sample covers 2016–2019 and consists of 67 listed issuers. The paper uses the event study method based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Third, the positive effect of the subsidies was significantly smaller in the transportation sector. Finally, we also confirmed that our results are same when we use the Fama and French (1993) three factor (FF3) model to apply for ESM as in previous studies (Jin and Zhang 2023;Sakawa and Watanabel 2023). Our results are robust when we apply the alternative FF3 model.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Third, the positive effect of the subsidies was significantly smaller in the transportation sector. Finally, we also confirmed that our results are same when we use the Fama and French (1993) three factor (FF3) model to apply for ESM as in previous studies (Jin and Zhang 2023;Sakawa and Watanabel 2023). Our results are robust when we apply the alternative FF3 model.…”
Section: Introductionsupporting
confidence: 89%
“…We introduced a typical firm from each sectors. Fourthly, we also used the FF3 model to confirm the robustness of our results, similar to previous studies (Jin and Zhang 2023;Sakawa and Watanabel 2023). To use the alternative methodology of the FF3 model, we investigated whether the conclusion of ESM based on two different models are robustly confirmed.…”
Section: Estimation Windowsupporting
confidence: 63%